Dietary resource partitioning in Anuran larvae in forested and open areas in Unimas campus, Sarawak - Siti zubaidah, Ismail. (Universiti Malaysia Sarawak (UNIMAS), 2007)
~ study on dietary resource partitioning in anuran larvae was conducted at Unimas Campus, Sarawak between August, ~OO6 to February, 2007. The diets of tadpoles of seven anuran species were examined to determine whether dietary ~ource partitioning occurs and whether the degree of dietary similarity is related to taxonomic affinity. A secondo bjective was to determine whether tadpoles of each species consume different food types in different microhabitat~pes. Three species from an open waterway and four species from a forested area, representing two families (Ranidae~nd Rhacoph ridae) were studied. Microalgae is the most dominant dietary component in intestinal samples of all~dpoles from bolh habitat categories. Dietary resource partitioning was found to be an important factor influencing the ~pes of prey con umed by tadpoles, allowing the coexistence of closely-related species.